Unearthing Talent and Building Character: The Role of Sports Education in Youth Interest and Participation - Usman, Arifuddin; Arifuddin, Muhammad Tauhid Al Islamy; Hudain, Muh Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This research is time-sensitive because Sinjai Regency has great potential for establishing leading sports, yet teenage sports participation is low. This study examines adolescents' interest and engagement in potential sports, identifies influencing factors, and compares subjective interest with actual sports participation. This study will also make strategic recommendations for local governments and sports institutions to develop sports based on local potential and teenage preferences. The method used is a descriptive quantitative approach involving adolescent respondents aged 13–18 years in various sub-districts in Sinjai Regency. Data collection techniques were carried out through closed questionnaires and semi-structured interviews distributed to junior high and high school students, and data triangulation was carried out through interviews with physical education teachers, coaches, and local sports figures. Data was analyzed using descriptive statistics and correlation analysis to examine the relationship between levels of interest, participation, and the factors that influence them. The results show that adolescent interest in potential sports such as soccer, volleyball, and athletics is relatively high, but not always followed by a commensurate level of participation. Dominant factors influencing participation include sports facilities, social support, and intrinsic motivation. The alignment between interest and actual involvement still needs to be strengthened through coaching programs and competitive activities at the school and community levels. In conclusion, interest-based strategies, environmental support, and the availability of adequate facilities are necessary to increase youth participation in sports in Sinjai Regency.